Cytomegalovirus infection in an immunocompetent host presenting as haemophagocytic lymphohistiocytosis - Inês Matias-Lopes; Henrique Atalaia Barbacena; Margarida Guiomar; Raquel Soares; Catarina Barão; Ana Rita Ferreira; Federica Parlato; Patrícia Howell-Monteiro (European Journal of Case Reports in Internal Medicine)
Cytomegalovirus (CMV) is a human herpes virus with a worldwide seroprevalence of 60-100%, mainly known to cause severe life-threatening disease in immunocompromised patients. In immunocompetent hosts (IMCh), CMV causes a self-limiting mononucleosis-like infection, and severe pictures are less recognized. We report a case of a previously healthy 62-year-old woman evaluated in the Internal Medicine outpatient clinic for 3 weeks of progressive fatigue, generalised inflammatory arthralgias, hypogastric discomfort and daily persistent fever. On first examination, paleness and hepatomegaly were noted. Further evaluation showed the presence of haemolytic anaemia; lymphocytosis and monocytosis; thrombocytosis; elevated C-reactive protein; hypertriglyceridemia and hyperferritinaemia; peripheral blood immunophenotyping with a 44% population of T cells and diminished CD4/CD8 ratio. Hemophagocytic lymphohistiocytosis (HLH) was suspected, with an Hscore of 190 points, giving a 70-80% probability. CMV serology was positive for acute infection (IgM positive/IgG negative), with a viral load of 4470 IU/ml. CMV primary infection was admitted, complicated with haemolytic anaemia, cholestatic hepatitis and possible HLH. Despite the laboratory frame exuberance, the patient remained stable and was discussed with Infectious Diseases, deciding not to initiate antiviral therapy. Over the next month, the fever, anaemia and hepatitis resolved, and the white blood cell count normalized. After two months, the CMV viral load was negative, and seroconversion was documented. Primary CMV infection is unusual in older patients. Additionally, in IMCh infection is usually mild, and severe infections are rare. In such cases, the use of antiviral therapy is not well established, and risk/benefit must be considered in a personalised approach. Altogether, the clinical and laboratory presentation of this case reinforces the need for high clinical suspicion.